Gamification and Its Potential for Reducing School Stress: Ecuadorian General Basic Education Institution Case - Mora Erazo, Gloria Yessenia (2023)
As the main objective of this work, the researchers aimed to reduce stress through gamified methodological strategies. Regarding the methodology, it consists of a quantitative one, with a quasi-experimental and explanatory design. Moreover, the authors selected a sample of 44 students from the eighth year of general basic education, aged 11 to 16 years, and used as an instrument for the pre-test and post-test the SISCO SV-21 survey (SIStémico Cognoscitivista, by its acronym in Spanish). This instrument allowed the researchers to diagnose the level of stress and evaluate the results obtained after the application of gamified methodological strategies. The results not only indicated an initial stress level of students between moderate and severe, but also reflected that the main concern was the lack of strategies to cope with challenging situations that generate stress. Therefore, the authors propose five strategies based on gamification for teaching tools to reduce stress and control stressful situations. This led to the post-test students obtaining a mild stress level, with fewer triggers for physiological and psychological symptoms. In conclusion, the suggested strategies based on gamification constitute a significant alternative for the reduction of student stress since they provide the means to face stressful events of schooling and reduce physical and psychological reactions that could hinder learning. Thus, the researchers recommend applying the proposed model of gamified methodological strategy in other educational contexts, inside the classroom, and with different topics to continue gathering results on its functionality in the dynamization of the teaching and learning process.